Donations to US based NGOs in international development cooperation: How (un-)informed are private donors? - Peter Nunnenkamp; Hannes Öhler (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2010)
Apart from scaling up foreign aid by NGOs, informed choices of private donors could also encourage an efficient and targeted use of NGO funds in international development cooperation. We assess the determinants of private donations across a large sample of US based NGOs with foreign aid activities. OLS and 2SLS estimations indicate that donors hardly make use of publicly available information on NGO characteristics, notably the price of giving and the degree of specialization, when deciding on donations. They rather rely on the frequently offered option to designate donations to preferred purposes - even though this behavior would be rational only under conditions that are unlikely to hold.
Keywords: L31; F35; D80; 330; non-governmental organizations; specialization; private donations; informed choices; price of giving; option to designate; Spende; Informationsverhalten; Konsumentenverhalten; Private Entwicklungshilfe; USA